2018
DOI: 10.33545/gynae.2018.v2.i2b.66
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of early onset pre-eclampsia v/s late onset pre-eclampsia

Abstract: Introduction: Preeclampsia is a multi-system disorder of unknown etiology that is unique to human pregnancy and is characterized by abnormal vascular response to placentation associated with increased systematic vascular resistance (SVR), enhanced platelet aggregation, activation of coagulation system and endothelial dysfunction. It remains a major cause of maternal and fetal/neonatal morbidity and mortality. Methodology: As per case record form thorough clinical examination including BP, edema, pallor etc was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Kari Annapurna et al [22] observed 57.6% Caesarean section. In another study 43% delivered by Caesarean section [26]. It is more when compared with other studies by Singh et al (21.4%) [19] and Rathore R, Butt NF et al [27] (15%).…”
Section: Discussionmentioning
confidence: 70%
“…Kari Annapurna et al [22] observed 57.6% Caesarean section. In another study 43% delivered by Caesarean section [26]. It is more when compared with other studies by Singh et al (21.4%) [19] and Rathore R, Butt NF et al [27] (15%).…”
Section: Discussionmentioning
confidence: 70%